2022
DOI: 10.1007/s00376-022-2048-8
|View full text |Cite
|
Sign up to set email alerts
|

On the Influences of Urbanization on the Extreme Rainfall over Zhengzhou on 20 July 2021: A Convection-Permitting Ensemble Modeling Study

Abstract: This study investigates the influences of urban land cover on the extreme rainfall event over the Zhengzhou city in central China on 20 July 2021 using the Weather Research and Forecasting model at a convection-permitting scale [1-km resolution in the innermost domain (d3)]. Two ensembles of simulation (CTRL, NURB), each consisting of 11 members with a multi-layer urban canopy model and various combinations of physics schemes, were conducted using different land cover scenarios: (i) the real urban land cover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 53 publications
4
14
0
Order By: Relevance
“…Our result indicated that the strong low‐level easterly airflow between the WPSH and Typhoon In‐Fa plays an essential role in the HnHRE, which is supported by some recent research (Deng et al., 2022; Luo et al., 2022; Y. Nie & Sun, 2022). Unique from the previous literature, the contribution of the WPSH and In‐Fa to the HnHRE is reasonably and quantitatively evaluated in this study, which pointed out that the HnHRE occurred with the aid of the highly favorable configuration of WPSH and In‐Fa circulations and their cooperation.…”
Section: Summary and Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our result indicated that the strong low‐level easterly airflow between the WPSH and Typhoon In‐Fa plays an essential role in the HnHRE, which is supported by some recent research (Deng et al., 2022; Luo et al., 2022; Y. Nie & Sun, 2022). Unique from the previous literature, the contribution of the WPSH and In‐Fa to the HnHRE is reasonably and quantitatively evaluated in this study, which pointed out that the HnHRE occurred with the aid of the highly favorable configuration of WPSH and In‐Fa circulations and their cooperation.…”
Section: Summary and Discussionsupporting
confidence: 89%
“…Our result indicated that the strong low-level easterly airflow between the WPSH and Typhoon In-Fa plays an essential role in the HnHRE, which is supported by some recent research (Deng et al, 2022;Luo et al, 2022;Y. Nie & Sun, 2022).…”
Section: Summary and Discussionsupporting
confidence: 88%
“…For example, on July 19–20, 2016, an extensive extreme rainfall event swept across North China, causing 139 human fatalities, 141,000 house collapses, and 718,000 ha of crops damages over the region, leading to a direct economic loss of 10 billion RMB (Xia & Zhang, 2019). More severely, the “21·7” extreme rainfall in Henan caused devastating floods, with a record‐breaking hourly rainfall rate of 201.9 mm hr −1 , leaving 398 human fatalities and a direct economic loss of 120.06 billion RMB (Luo et al., 2022; Su et al., 2021; Wei et al., 2022; Yin et al., 2022), which has brought unprecedented attention to extreme rainfall events. Early warning and forecasting are always a crucial part of disaster prevention and mitigation.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond local orographic conditions, it is believed that other factors, such as land use and land cover properties, can also play a role in extreme precipitation event (Pielke Sr et al., 2011). Yet, limited attention has been paid to the potential impacts of local land properties on the record‐breaking “July‐20 event” (Luo et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Beyond local orographic conditions, it is believed that other factors, such as land use and land cover properties, can also play a role in extreme precipitation event (Pielke Sr et al, 2011). Yet, limited attention has been paid to the potential impacts of local land properties on the record-breaking "July-20 event" (Luo et al, 2022).Drastic land cover conversion has occurred in China in the past 40 years, and urban area expansion was one of the major types of land conversion (Liu et al, 2020). The most spectacular urban expansion was certainly in the low-lying coastal zone (e.g., agglomerations in the region of Beijing-Tianjin-Hebei, in the Yangtze River Delta, and the Pearl River Delta), but central China including Henan province has experienced accelerating urbaniza-…”
mentioning
confidence: 99%